Penyakit Keriting Daun Pepaya yang Disebabkan oleh Cladosporium cladosporioides - Widodo .; Suryo Wiyono (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Leaf curling and chlorotic spot on young leaves of papaya type California was observed in Bogor, Kebumen, and Bekasi. Conidium of Cladosporium cladosporioides was found associated with diseased tissue based on microscopic examination. To our knowledge, this is the first report of C. cladosporioides causing papaya leaf curling in Indonesia. Key words: chlorotic, leaf curl disease, papaya disease, scab